PERAN HUKUM INTERNASIONAL DALAM MENJAGA HUBUNGAN ANTAR BANGSA - Sihotang, Kristin Magdalena (Universitas Pendidikan Ganesha, 2022)
Fundamentally, worldwide regulation is state regulation, and global regulation is called highway regulation. The law of countries is a gathering of customs and legitimate standards that were active in the connections between lords in old times. International regulation or likewise regularly alluded to as public regulation shows the intricacy between the guidelines and rules that oversee the connection between individuals from a general public, like states or states.In this way, things that support participation and relationships around the world become valuable. The exploratory techniques used in this diary are taken from various sources, both on the web and print media, which can help support an article and towards the end the author provides an ending. For that the author wants to equalize the perception of where the law comes from. In short, the source of the law itself is anything that creates binding and coercive regulations, so that if these regulations are violated, it will have fatal consequences and real sanctions for violators. Sources of law imply the origin of law and where it comes from.In addition, there are many sources of international law, including: (1) International treaties; (2) International customs; (3) General legal concepts; (4) Court decisions; and (5) Teachings of the greatest scholars from different nations. Sources of international law are referred to in international law as the actual documents that international legal specialists study to ascertain whether law is relevant for a specific event or occurrence.